Cyclitol based metal complexing agents. preference for the extraction of lithium by myo-inositol based crown-4-ethers depends on the relative orientation of crown ether oxygen atoms - Dixit, Shailesh S.; Shashidhar, M. S.; Devaraj, Subramanian (Tetrahedron, 2006)
myo-Inositol derived crown-4-ethers in which two of the oxygen atoms in the crown ether moiety have different relative orientations were prepared. Metal picrate binding studies revealed that the crown ether having 1,3-diaxial orientation shows the highest selectivity for binding to lithium although the crown ether having 1,2-diequatorial orientation exhibited the highest binding constant for lithium picrate. These results suggest that relative binding affinity of metal ions to crown ethers can be tuned by varying the relative orientation of crown ether oxygen atoms. The relevance of these results to the previously observed regioselectivity during the O-substitution of myo-inositol orthoesters is discussed. (c) 2606 Elsevier Ltd. All rights reserved.
Keywords: crown ether; Cyclitol; Inositol; ligand; lithium; metal complex

Inositol derived crown ethers: effect of auxiliary protecting groups and the relative orientation of crown ether oxygen atoms on their metal ion binding ability - Dixit, Shailesh S.; Shashidhar, Mysore S. (Tetrahedron, 2008)
The binding constants of crown ethers prepared from tetra-O-substituted myo- and scyllo-inositol derivatives and 2-O-substituted myo- and scyllo-inositol-1,3,5-orthoformates, with metal picrates show that the O-substituents and the relative orientation of the crown ether oxygen atoms contribute significantly to the binding of crown ethers with metal ions. In particular, the binding efficiency of myo-inositol derived crown ethers to silver and potassium ions could be enhanced by introducing benzyl ethers in the inositol ring. Hence binding efficacy and selectivity of metal ions to inositol derived crown ethers can be tuned by varying substituents on the myo-inositol ring and/or the relative orientation of crown ether oxygen atoms. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: crown ether; Cyclitol; Inositol; ligand; metal complex; supramolecule

Protein ligand complex guided approach for virtual screening - Karthikeyan, Muthukumarasamy; Pandit, Deepak; Vyas, Renu (Combinatorial Chemistry & High Throughput Screening, 2015)
The target ligand association data is a rich source of information which is not exploited enough for drug design efforts in virtual screening. A java based open-source toolkit for Protein Ligand Network Extraction (J-ProLiNE) focused on protein-ligand complex analysis with several features integrated in a distributed computing network has been developed. Sequence alignment and similarity search components have been automated to yield local, global alignment scores along with similarity and distance scores. 10000 proteins with co-crystallized ligands from pdb and MOAD databases were extracted and analyzed for revealing relationships between targets, ligands and scaffolds. Through this analysis, we could generate a protein ligand network to identify the promiscuous and selective scaffolds for multiple classes of proteins targets. Using J-ProLiNE we created a 507 x 507 matrix of protein targets and native ligands belonging to six enzyme classes and analyzed the results to elucidate the protein-protein, protein-ligand and ligand-ligand interactions. In yet another application of the J-ProLiNE software, we were able to process kinase related information stored in US patents to construct disease-gene-ligand-scaffold networks. It is hoped that the studies presented here will enable target ligand knowledge based virtual screening for inhibitor design.
Keywords: Complexes; ligand; protein; scaffolds; sequences; similarity score; virtual screening

Thiol and halometallate, mutually passivated quantum dot ink for photovoltaic application - Mandal, Debranjan; Goswami, Prasenjit N.; Rath, Arup K. (ACS Applied Materials & Interfaces, 2019)
Tunable-band-gap colloidal QDs are a potential building block to harvest the wide-energy solar spectrum. The solution-phase surface passivation with lead halide-based halometallate ligands has remarkably simplified the processing of quantum dots (QDs) and enabled the proficient use of materials for the development of solar cells. It is, however, shown that the hallometalate ligand passivated QD ink allows the formation of thick crystalline shell layer, which limits the carrier transport of the QD solids. Organic thiols have long been used to develop QD solar cells using the solid-state ligand exchange approach. However, their use is limited in solution-phase passivation due to poor dispersity of thiol-treated QDs in common solvents. In this report, a joint passivation strategy using thiol and halometallate ligand is developed to prepare the QD ink. The mutually passivated QDs show a 50% reduction in shell thickness, reduced trap density, and improved monodispersity in their solid films. These improvements lead to a 4 times increase in carrier mobility and doubling of the diffusion length, which enable the carrier extraction from a much thicker absorbing layer. The photovoltaic devices show a high efficiency of 10.3% and reduced hysteresis effect. The improvement in surface passivation leads to reduced oxygen doping and improved ambient stability of the solar cells.
Keywords: ligand; mobility; quantum dot; solar cell; surface passivation

Tale of biphenyl and terphenyl substituents for structurally diverse ketiminato magnesium, calcium and germanium complexes - Kumar, Rohit; Yadav, Sandeep; Gour, Kritika; Sangtani, Ekta; Ranjan Dash, Soumya; Raja, Abhishekram; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Chemistry-An Asian Journal, 2020)
In this paper, we have used two N,O-ketiminato ligands (L1 and L2) with biphenyl and terphenyl substituent on the nitrogen atom. Deprotonation of L1 with KN(SiMe3)(2) and subsequent reaction with MgI2 led to a homoleptic dinuclear magnesium complex (1) with a Mg2O2 four-membered ring. Deprotonation with nBuLi and subsequent reaction with MgI2 afforded a unusual dinuclear magnesium complex (2) with a Mg2O2 ring. Extension of the ligand for calcium resulted in a trinuclear calcium complex (3) with six four-membered Ca2O2 rings. We could not isolate any chelating complex when L2 was used as a ligand, and only oxygen bound magnesium (4) and calcium (5) adducts were isolated. DFT studies were performed to understand this dissimilar behavior. More diverse results were obtained when lithiated L1 and L2 were treated with germanium dichloride. We were able to stabilize a monomeric germylene monochloride (7) with L1. However, with L2, an unusual ligand scrambling, and a C-C coupling take place, leading to the formation of a secondary carbocation with GeCl3- as a counter-anion (8). Besides, a germanium dichloride adduct (9) bound to the oxygen center of the ligand was obtained as the minor product.
Keywords: calcium; Germylene; ligand; Magnesium; X-ray Structure

Crack-free conjugated PbS quantum dot-hole transport layers for solar cells - Sharma, Ashish; Dambhare, V. Neha; Bera, Jayanta; Sahu, Satyajit; Rath, Arup K. (ACS Applied Nano Materials, 2021)
Colloidal quantum dots (QDs) benefit from solution-phase processing and band-gap tuning for their application in solar cell development. Today's QD solar cells rely on solid-state ligand exchange (SLE) to replace bulky oleic acid (OA) ligands with small 1,2-ethanedithiol (EDT) ligands to develop a conducting hole transport layer (HTL). High volume contraction in EDT conjugated QD films, however, leads to crack and porosity in the HTL, which is a major cause of concern for the device reproducibility and large-area solar cell development. We show that partial removal of the OA ligands in the solution phase reduces the volume contraction in solid films, thereby allowing the growth of crack-free QD films in the SLE process. The cleaning of QDs by repeated precipitation and redispersion using a protic methanol (MeOH) solvent helps with partial removal of the OA ligands, but it is detrimental to the electronic properties of QDs. We develop a one-step solution-phase partial ligand-exchange process using ammonium salts, which enable partial replacement of the OA ligands and passivation of the QD surface. Introduction of the facile partial ligand-exchange process eliminates the need for tedious and wasteful multiple cleaning steps with MeOH, while improving the photophysical properties of QDs. The advancement in QD processing helps to build crack-free, smooth, and conjugated QD films for their deployment as HTLs in solar cell development. Partial ligand exchange with NH4SCN leads to a 1.5 times increase in p doping and mobility over multiple MeOH-cleaned PbS QD films. HTLs developed using NH4SCN QDs show an improved photovoltaic performance to attain a 10.5% power conversion efficiency. Improvement in the depletion width and hole collection efficiency leads to a superior photovoltaic performance, as confirmed from experimental studies and one-dimensional solar cell capacitance simulation.
Keywords: Efficiency; ligand; polydispersity; quantum dot; solar cells; thin film

Reduction of hydroxyl traps and improved coupling for efficient and stable quantum dot solar cells - Mandal, Debranjan; Dambhare, V. Neha; Rath, Arup K. (ACS Applied Materials & Interfaces, 2021)
Progress in quantum dot (QD)-based solar cells has been underpinned by the improvements in surface passivation and advancements in device engineering. Acute control over the surface properties is crucial to restrict the formation of in-gap trap states and improve the QD coupling in achieving conducting QD films. In this report, we demonstrate a solution-phase hybrid passivation strategy, which is beneficial in removing detrimental hydroxyl traps and improving the coupling between QDs by reducing the interdot distance. Advancement in surface passivation is translated to the long carrier lifetime, higher carrier mobility, and superior protection toward degradations in QD solids. The performance of solar cell devices is increased by 26% to reach an efficiency of 10.6%, compared to the state-of-the-art lead halide passivated solar cells. The improvement in solar cell performance is supported by the reduction of trap states and an 80 nm increase in thickness of the light-absorbing QD layer.
Keywords: ligand; mobility; quantum dot; solar cell; surface passivation